Light alloys from traditional alloys to nanocrystals - Polmear, I. J. (Elsevier/Butterworth-Heinemann, 2006)
The definitive overview of the science and metallurgy of aluminum, magnesium, titanium and beryllium alloys, this is the only book available covering the background materials science, properties, manufacturing processes and applications of these key engineering metals in a single accessible volume. Use of these metals is now more widespread than ever, and they are routinely found in motor vehicles and aircraft. New material includes materials characteristics and applications; heat treatment properties; fabrication; microstructure/property relationships; new applications and processes. *The definitive single volume overview *New material on processing, characteristics and applications of these essential metals *Covers the latest applications and processes in the auto and aero industries.
Previous ed.: London: Arnold, 1995.
Keywords: Light metals -- Metallurgy.; Light metal alloys.; elektronické knihy; electronic books